Sky without stars - Brody, Jessica; Rendell, Joanne (System Divine, 2019)
"This sweeping reimagining of Les Misérables tells the story of three teens from very different backgrounds who are thrown together amidst the looming threat of revolution on the French planet-colony of Laterre"--